Analysis of the Implementation of Merdeka Learning Curriculum in Physics Lessons at State Senior High Schools in Bengkulu City - Pranesti Nita Utami (CV Media Inti Teknologi, 2023)
The purpose of this study is to introduce the Merdeka learning curriculum to Bengkulu City's Public Senior High School. The research's data came from a review of the literature, interviews with the deputy head of curriculum, a physics instructor, and class X students at SMAN 8 Bengkulu City, SMAN 6 Bengkulu City, and SMAN 2 Bengkulu City. The descriptive qualitative approach was the research strategy employed. The methods used to acquire the data were interviews, observations, and literature reviews. Interview and observation sheets made up the research tools. The use of qualitative data analysis is one method of data analysis. Based on observations and interviews, the school's implementation of the autonomous learning curriculum has not gone as well as it could have. The study concludes that there are several challenges in implementing the autonomous learning curriculum in Physics classes, and there are modifications in the curriculum from the 2013 curriculum to the autonomous curriculum.